2012
DOI: 10.1002/jmri.23575
|View full text |Cite
|
Sign up to set email alerts
|

Does the amplatzer septal occluder device alter ventricular contraction pattern? A ventricular motion analysis by MR tagging

Abstract: Purpose: To assess by cardiovascular magnetic resonance (CMR) and CMR tagging if the Amplatzer Septal Occluder affects right ventricular (RV) and left ventricular (LV) motion pattern. Materials and Methods:Sixteen consecutive patients with significant atrial septal defect (ASD) and nine consecutive patients with persistent foramen ovale (PFO) as controls were studied before and a median of 14 days after defect closure by an Amplatzer occluder. By CMR enddiastolic (EDV) and end-systolic (ESV) RV and LV volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the RV contraction takes time to recover completely after eliminating a left‐to‐right shunt . Additionally, the permanent implantation of an occluder in the atrial septum may acutely influence the RV contraction postprocedure, particularly in younger children …”
Section: Introductionmentioning
confidence: 99%
“…However, the RV contraction takes time to recover completely after eliminating a left‐to‐right shunt . Additionally, the permanent implantation of an occluder in the atrial septum may acutely influence the RV contraction postprocedure, particularly in younger children …”
Section: Introductionmentioning
confidence: 99%
“…Of the studies on left ventricular rotation after interventional shunt closure, two showed results different to those of our study. In a study population of predominantly adult patients with persistent foramen ovale and atrial septal defects, 27 cardiac magnetic resonance tagging showed a decline in basal and apical rotation after device closure, resulting in stable maximal torsion. Another study on adults reported an increase in maximal torsion after intervention, with improved untwisting after the procedure on speckle tracking 28 .…”
Section: Discussionmentioning
confidence: 96%
“…Of the studies on left ventricular rotation after interventional shunt closure, two showed results different to those of our study. In a study population of predominantly adult patients with persistent foramen ovale and atrial septal defects, 27 cardiac magnetic resonance tagging showed a decline in basal and apical rotation after device closure, ns 5 statistically non-significant; PDA 5 patent arterial duct; Rot apex 5 peak systolic apical rotation; Rot basis 5 peak systolic basal rotation; Tor 5 maximal torsion; Torrate dia 5 peak diastolic torsion rate; Torrate sys 5 peak systolic torsion rate; post 5 after intervention; pre 5 before intervention Maximal and minimal values of the mean rotational curves of apical and basal short-axis loops and torsional parameters resulting from subtraction of the apical from the basal rotational curves Results in mean 6 SD Differences between patient data using paired t-test and patient and control group data compared using the unpaired t-test Figure 7.…”
Section: Glsmentioning
confidence: 99%
“…Atrial septum device misplacements are reported as rare, but the devices are rarely controlled by TEE post insertion ( 26 30 ). TTE may reveal transient changes in left atrial passive emptying and strain ( 31 ), while left ventricular function is not affected when assessed by magnetic resonance imaging (MRI) ( 32 ). However, as in our case, TTE may not reveal displaced devices or even remaining defects in the PFO.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective longitudinal multicenter study of 199 patients, “DysrhythmiAs in patieNts with congenitAl heaRt diseAse” (DaNaRA), demonstrated that patients with congenital heart disease, particularly patients with complex defects, develop AF at a young age and progress frequently from paroxysmal AF to (long-standing) persistent/permanent AF ( 91 ). Sixteen patients (8%) experienced a cerebrovascular event 14 ( 2 33 ) years before the first documented AF. The total incidence of TIA/stroke in the population was 13%.…”
Section: Discussionmentioning
confidence: 99%